Manual de treinamento em Inteligência Emocional - Tavela Júnior, José Sérgio (2018)
Emotional intelligence (EI) can be understood as the ability to recognize and manage one's own and other people's emotions. Studies show that people with higher levels of IE have a higher chance of success in personal and professional life. Specifically in Medicine, students with higher levels of IE can demonstrate better academic performance compared to students with less training of these skills. EI can also influence the physician-patient relationship and the stress related to professional practice. Currently, IE is considered as a set of skills, which may be taught and improved. The objective of this manual is to describe IE training techniques that can be used in undergraduate health sciences courses. The following techniques were described: metallization, anchor, referential experience, case-based learning, Balint group, reflective portfolio and role-play.